FEATURES OF ACCOUNTING ORGANIZATION OF LIABILITIES FOR TAXES AND DUTIES UNDER CIRCUMSTANCES OF ENVIRONMENTAL POLICY IMPLEMENTATION IN UKRAINE - T. Murovana (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The main problems of accounting organization of liabilities for taxes and duties under current complicated economic and environmental conditions were investigated. Measures for improving tax calculation reflecting, environmental tax and other environmental liabilities in accounting, tax and financial reporting in order to simplify the accounting process, improve organization of business activities, ensure implementation of environmental policy balance were developed.